The role of sustainable marketing in building customer relationships – A field study for a number of engineering and design companies – - Abd Alhasan, Shahlaa Ali (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims to examining the relationship between the dimensions of sustainable marketing represented by ethics and social marketing responsibility and its role in building customer relations through value and customer satisfaction from the point of view of marketers, and launched the importance of research on determining the importance of both marketing ethics and social responsibility in building customer relationships. The research sample included (40) marketing people in a number of engineering and design companies and the questionnaire was adopted to poll the sample opinions. The extracted data was analyzed using a set of computerized statistical analysis tools with a statistical system to test the hypotheses, and the practical side included the most important statistical means the arithmetic mean, standard deviation, correlation, and simple and multiple regression where the research was based On two hypotheses, the first main hypothesis is that there is a statistically significant correlation between sustainable marketing and building customer relationships, and the second main hypothesis is that there is a significant significant impact relationship between sustainable marketing and building customer relationships, The most important conclusions were the high level of awareness of the individuals under consideration of the importance of the sustainable marketing dimensions represented in marketing ethics and social responsibility, as well as focusing on building customer relationships by raising the value of the customer and trying to gain his satisfaction, and based on the results reached, the research set a set of proposals, the most important of which was to raise the level of responsibility Social services in companies with the aim of raising the value of the customer and gaining his satisfaction.
Keywords: sustainable marketing; marketing ethics; social responsibility; building customer relationships; customer satisfaction; customer value